Hematocrit and the incidence of stroke: a prospective, population-based cohort study - Yang R; Wang A; Ma L; Su Z; Chen S; Wang Y; Wu S; Wang C (Dove Medical Press, 2018)
Renling Yang,1,2 Anxin Wang,3–6 Li Ma,2 Zhaoping Su,7 Shuohua Chen,8 Yilong Wang,3–6 Shouling Wu,8 Chen Wang1,2 1Department of General Practice, School of General Practice and Continuing Education, Capital Medical University, Beijing, China; 2Department of General Practice, Beijing Tiantan Hospital, Capital Medical University, Beijing, China; 3Department of Neurology, Beijing Tiantan Hospital, Capital Medical University, Beijing, China; 4China National Clinical Research Center for Neurological Diseases, Beijing, China; 5Center of Stroke, Beijing Institute for Brain Disorders, Beijing, China; 6Beijing Key Laboratory of Translational Medicine for Cerebrovascular Disease, Beijing, China; 7Department of Epidemiology and Health Statistics, Academy of Public Health and Management, Weifang Medical University, Weifang, China; 8Department of Cardiology, Kailuan Hospital, North China University of Science and Technology, Tangshan, China Background and purpose: Whether higher hematocrit levels could increase the incidence of stroke has always been full of controversy. This study aimed to explore the association between hematocrit and the incidence of stroke in the Chinese population.Subjects and methods: The Kailuan study is a prospective longitudinal cohort study on risk factors and events of chronic diseases. Using a multivariable Cox proportional hazards analysis, we examined the association between baseline hematocrit values and the incidence of stroke in the Kailuan cohort (93,299 participants).Results: A total of 3,624 participants developed stroke during the 9-year follow-up period. In Cox regression models adjusted for demographic information and for clinical variables, there was a significant association between baseline hematocrit levels and the incidence of stroke. The highest hematocrit quartile (quartile 5: men, hematocrit >48.6%; women, hematocrit >43.2%) was associated with a higher incidence of stroke (HR 1.17, 95% CI 1.04–1.31, P for trend =0.0016) compared with the lowest hematocrit quartile (quartile 1: men, hematocrit <41.5%; women, hematocrit <36.6%). In the analysis of ischemic stroke, intracerebral hemorrhage separately, similar association was observed in ischemic stroke, but there were no statistical differences in intracerebral hemorrhage.Conclusion: Higher hematocrit levels are associated with a higher incidence of stroke in the Chinese population. Keywords: hematocrit, stroke, cohort